(untitled) (Ágora Journal, 2024)
May 13th is the main event celebrated by the Quilombola Community of Monte Alegre, Brazil, formed during the transition from slavery to freedom in the city of Cachoeiro de Itapemirim. This was the main concentration point for enslaved people in Espírito Santo state in the second half of the 19th century. In the oral tradition of Monte Alegre, abolition is the dividing line between slavery time and (official) freedom time, which is symbolically represented in the jongo that inspired this study’s title. Therefore, it is no coincidence that the event is narrated in detail. The community is certified since 2005 as a quilombo remnant, and is highlighted as a memory of slavery, which is accessed in the construction of quilombola identity. Its local significance partially explains the local perpetuation of May 13th instead of November 20th, popularized after Law no. 10.639/2003 with a significant local impact. As a bearer of a genealogical memory of the slavery experienced in the territory occupied by their ancestors since the mid-1800s, the local characters, places and events are highlighted in the interviews conducted according to Oral History guidelines. Their narrative emphasizes the significance of abolition for their ancestors, who celebrated the "dawn of freedom" as a possibility of freedom and protection for their bodies, their families and their way of life.